Inequalities in worsening work and income decrease/cessation in SARS-CoV-2 infection in adults and elderly people: the population-based SulCovid-19 study - Yohana Pereira Vieira; Lara dos Santos Camilo; Évelyn Sousa Araújo; José Drummond de Macedo Neto; Letícia Lima Junqueira; Karla Pereira Machado; Tatiane Nogueira Gonzalez; Rosália Garcia Neves; Suele Manjourany Silva Duro; Mirelle de Oliveira Saes (BMC Public Health)
Abstract Objective To evaluate inequalities in the worsening of work and income decrease/cessation among adults and elderly people with COVID-19 in the extreme south of Brazil. Methods This is a cross-sectional study based on the SulCovid-19 study carried out with adults and elderly people infected with SARS CoV-2 from December/2020 to March/2021 in the municipality of Rio Grande, RS, Brazil. The outcomes were: “worsening of work” and “income decrease/cessation” following COVID-19. The independent variables were gender, skin color, income, education, health insurance, age, marital status, schooling, morbidities, hospitalization and long COVID. Results prevalence of worsening work was 33.7% (95%CI 31.8; 35.5), while prevalence of income decrease/cessation was 44.6% (95%CI 42.7; 46.6). Female individuals with income in dollars between US0.00 and US192.0 had 13.0% (95% CI 1.01; 1.27) and 22.0% (95% CI 1.02; 1.46) greater prevalence of losing work and were 22.0% (95% CI 1.12; 1.34) and 49.0% (95% CI 1.31; 1.70) more likely to suffer a decrease/cessation of their income. Individuals with long COVID had 46.0% greater prevalence (95% CI 1.27; 1.68) of worsening at work and 24.0% (95% CI 1.13; 1.37) greater prevalence of income decrease/cessation when compared to those without the disease. Individuals with 3 symptoms or more had 86.0% (95% CI 1.58; 2.20) greater prevalence of worsening work and 47.0% (95% CI 1.31; 1.65) greater prevalence of income decrease/cessation when compared to those without long COVID symptoms. Conclusions There was inequality in the worsening of work and income decrease/cessation for individuals infected with SARS CoV-2. Among these individuals, females, lower income, low education and greater long COVID severity were the most affected.